Studi Kelayakan Investasi Pembangunan Upstream Infrastructure Air Bersih Pdam Kota Pekanbaru Tahun 2015 - 2035 - Ito Tandika; Ari Sandhyavitri; Andy Hendri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru city is the capital of Riau province consisting of 12 sub-district with a total population in 2013 was 1.018.750 inhabitants. Currently PDAM "Tirta Siak" of Pekanbaru City served 10% of the water demand within the city area. The PDAM production capacity was 620 liters/sec. The purpose of this study are (i) to forecast the water demand in period of 2015-2035, (ii) calculate the investments of upstream infrastructure, and (iii) analyze the upstream infrastructure financial aspects using Benefit Cost Ratio(BCR) method, Net Present Value (NPV), Internal Rate of Return (IRR), Break Even Point (BEP), Payback Period, and Sensitivity Analysis.Result of this studies are (i) Pekanbaru City water demand for 2015 approximate to 4.056 liters/second and continued to rise become 9.176 liters / sec on 2035, (ii) the upstream infrastructure investments is divided into two phases with an investment for phase 1 is Rp. 571.059.228.117 and for phase 2 is Rp.602.641.569.713, and (iii) financial aspects values are BCR 1,37; NPV Rp.900.869.707.831; IRR 15.93% ; payback period is 18 years 4 months and 3 days ; and BEP value is 515.031.471 m3 of water that must be sold.Keyword : upstream infrastructure, water demand, investments, financial aspects